Efficiency of Phosphate Adsorption in Synthetic Wastewater using Mango Leaves Combined with Tap Water Treatment Plant Sludge - Noinumsai, Supawadee; Chada, Chatchai; Waipib, Sitthisak; Wachrirawongsakorn, Piyada (KKU Science Journal, 2026)
Phosphate is a major pollutant causing eutrophication in aquatic environments. Developing cost-effective and efficient adsorbent materials is crucial for wastewater treatment. This research aimed to investigate the efficiency of phosphate adsorption in synthetic wastewater using adsorbents prepared from tap water treatment plant sludge (S) mixed with mango leaves (LM) at ratios of 100:0, 70:30, 50:50, 30:70, and 0:100 by weight. The results showed that S-LM ratios of 100:0 and 70:30, calcined at 500ºC for 2 hours, could be successfully formed into pellets and were water-insoluble. The adsorbent surface was then modified by chitosan coating. The equilibrium time study revealed that 1.000 g of S-LM (70:30) adsorbent at room temperature and pH 7 reached adsorption equilibrium faster with chitosan coating (16 hours) compared to the uncoated adsorbent (24 hours). The adsorption efficiency study demonstrated that chitosan-coated adsorbents achieved higher removal efficiency than uncoated ones, with phosphate removal rates of 60.00% and 44.00%, respectively. The adsorption isotherm study showed that the highest correlation coefficient (R²) was 0.9910, close to 1.0, indicating excellent agreement with the Langmuir isotherm model and confirming monolayer adsorption behavior. The maximum adsorption capacity of S-LM (70:30)+C was 158.7302 mg/g for the chitosan-coated adsorbent and 14.7059 mg/g for S-LM (100:0). The chitosan-coated S-LM (70:30) adsorbent exhibited the highest efficiency due to the introduction of positively charged functional groups, particularly protonated amino groups (-NH3+), which attract negatively charged phosphate ions (PO43-) through electrostatic attraction mechanisms. This enhanced performance makes the adsorbent highly suitable for application in treating phosphate-contaminated wastewater.